The Effects of Selected Aerobic Exercises on Pulmonary Functions of High School Obese Girls - Khadijeh Irandoust (Shiraz University of Medical Sciences, 2015)
Background: Aerobic exercise is an important component of pulmonary functions for obese adolescents. There are few studies on aerobic exercise and pulmonary function in obese adolescence. Objectives: The purpose of this study was to investigate the effect of selected aerobic exercise training on some pulmonary function of Iranian obese girls. Patients and Methods: Forty-five, apparently obese adolescence, aged 14 - 15 years were randomly divided into three groups (15 subjects in each group) including rope skipping; jogging and control groups. Experimental groups participated in a twelve- week program (3 sessions a week, each session for 45 minutes) while control group had no plan of exercise. A spirometry test was taken 24 hours before and after the training protocol. Statistical analysis using the one-way analysis of variance was used (P < 0.05). Results: The results suggested that all anthropometric characteristics of both experimental groups including weight, body mass index (BMI), percent body fat (PBF), waist-hip ratio (WHR) were significantly improved after exercise protocol, furthermore, ventilation capacity (VC), forced vital capacity (FVC), forced expiratory volume in the first second (FEV1) were significantly improved in experimental groups compared to control group (P < 0.001), while no significant difference was found between two experimental groups in ventilation functions (P > 0.001). Conclusions: We conclude that appropriate aerobic exercise can improve lung function in obese adolescence.